Aulacid wasps (Hymenoptera: Aulacidae) of New Guinea, with descriptions of five new species - Jennings, John T.; Austin, Andrew D. (Zootaxa, 2006)
The little known aulacid fauna of New Guinea comprises six geographically isolated, endemic species. Previously known from a single species, Aulacus pterostigmatus (Szépligeti), three new species of Aulacus are described: A. enarotadi, A. sedlaceki and A. wau. In addition, Pristaulacus is recorded from New Guinea for the first time with the descriptions of P. kiunga sp. nov. and P. laloki sp. nov. A key to the New Guinea species is provided.